Early Maxillary Expansion with the Ni-Ti Memory Leaf Expander-A Compliance-Free Fixed Slow Maxillary Expansion Screw: A Report of 2 Cases - Bahar Ulug; Ayça Arman Özçırpıcı (Galenos Yayinevi, 2021)
Transversal problems such as crowding and crossbite are one of the most common problems dealt with in early orthodontic treatments. Early correction of these problems may ease or even eliminate the future need for treatment. This paper presents the management of 2 cases with transverse discrepancy using the Ni-Ti Memory Leaf Expander--a new compliance-free slow maxillary expansion appliance. The total treatment time for both cases was 9 months. In both cases, the inter-canine, inter-premolar, and inter-molar distances, as well as the arch length, have all increased.